Endemism and regionalization in the Andes: What do reptiles tell us? - Gómez, Juan Manuel Díaz (Zootaxa, 2025)
This study aims to establish a biogeographic regionalization of the Andes in South America through a quantitative analysis focused on reptile distributions. I compiled georeferenced data for 455 species, encompassing 34,192 records, and used two different methodologies to delineate bioregions and areas of endemism. The results reveal 17 bioregions that largely correspond with previously proposed subdivisions, although novel biogeographic units influenced by scale effects may be recognized. Also, 17 areas of endemism were identified, many aligning with key biogeographic provinces such as Puna, Atacama, and Patagonia, emphasizing the importance of reptiles as biogeographic indicators. My comparisons with existing biodiversity hotspots show an overlap with these proposals. The bioregions and areas of endemism, however, are more finely defined than the hotspots. I also compared those areas with areas found by a global regionalization for reptiles. The findings support the utility of quantitative, multi-taxon approaches to biogeographic regionalization, highlighting the complex and mosaic nature of the Andes biota. The existence of some bioregions that aren’t fully congruent with previous proposals suggests the existence of biogeographic patterns that have not yet been recognized. This work underscores the necessity of incorporating reptiles into biodiversity assessments and conservation planning to better capture the region’s endemic diversity and inform targeted protection strategies.